Pemberdayaan remaja putri dengan edukasi nutrisi pencegahan anemia melalui media e-leaflet - Sri Kurnia Dewi; M. Dodik Prasetyo; Dini Justian; Dhinny Novriyanti; M. Radi Pratama (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Anemia is a condition in which the red blood cell count or the concentration of hemoglobin (Hb) the oxygen-carrying component of blood is insufficient to meet the body's physiological needs. Empowering adolescents through nutrition education aimed at anemia prevention plays a crucial role in reducing the incidence of anemia among adolescent girls. Implementation can be achieved through various methods, including direct health promotion, social media, e-leaflets, and other media. Purpose: To improve adolescent girls' understanding and knowledge regarding nutrition for anemia prevention using e-leaflets. Method: This community service activity consisted of interactive education on nutrition and anemia for adolescent girls. The activity took place on Monday, July 20, 2026, at the MTs Manarulhuda Cianjur Hall, involving 147 female students as respondents and four students from STIKes Permata Nusantara. The educational session was conducted through lectures and interactive discussions supported by e-leaflets. Respondent knowledge and understanding were measured using a one-group pretest-posttest design, utilizing questionnaires administered before (pretest) and after (posttest) the educational activity. Evaluation involved data analysis and descriptive reporting to illustrate the distribution of respondents' knowledge levels before and after the health education session. An observational evaluation also served as a final assessment of the activity's achievements, alongside providing guidance to the school on delivering initial interventions to prevent anemia and its consequences. Results: The majority of respondents were 13 years old (n=83; 56.5%). Regarding knowledge levels concerning nutrition and anemia, there was a proportional increase in the